1999
DOI: 10.1038/43432
|View full text |Cite
|
Sign up to set email alerts
|

Genetic enhancement of learning and memory in mice

Abstract: Hebb's rule (1949) states that learning and memory are based on modifications of synaptic strength among neurons that are simultaneously active. This implies that enhanced synaptic coincidence detection would lead to better learning and memory. If the NMDA (N-methyl-D-aspartate) receptor, a synaptic coincidence detector, acts as a graded switch for memory formation, enhanced signal detection by NMDA receptors should enhance learning and memory. Here we show that overexpression of NMDA receptor 2B (NR2B) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

79
1,052
5
25

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,653 publications
(1,170 citation statements)
references
References 28 publications
79
1,052
5
25
Order By: Relevance
“…For example, overexpression of the NR2B subunit in mice results in enhanced learning and memory in several behavioral tasks, including fear conditioning and fear extinction (Tang et al, 1999). Further, blockade of NR2B-containing NMDARs with ifenprodil impairs synaptic plasticity in the amygdala without impairing routine neural transmission (Li et al, 1995;Weisskopf and LeDoux, 1999;Bauer et al, 2002), and ifenprodil also impairs fear acquisition without affecting its expression (Rodrigues et al, 2001;Blair et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of the NR2B subunit in mice results in enhanced learning and memory in several behavioral tasks, including fear conditioning and fear extinction (Tang et al, 1999). Further, blockade of NR2B-containing NMDARs with ifenprodil impairs synaptic plasticity in the amygdala without impairing routine neural transmission (Li et al, 1995;Weisskopf and LeDoux, 1999;Bauer et al, 2002), and ifenprodil also impairs fear acquisition without affecting its expression (Rodrigues et al, 2001;Blair et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…NR2B has been shown to be necessary for synapse formation and plasticity (Tang et al, 1999;Slutsky et al, 2004), whereas NR2A expression is associated with synaptic maturation (Fu et al, 2005). NMDAR made up of NR2B and NR1 subunits are the dominant form during …”
Section: Indexing Termsmentioning
confidence: 99%
“…Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999). Further, Roche et al (2001) have shown that the C-terminus of NR2B subunit is sufficient for rapid internalization of the NMDA receptor.…”
mentioning
confidence: 99%